U źródeł problematyki podmiotowości poznania. Krytyczne stanowisko Ksenofanesa z Kolofonu wobec poprzedzającej go tradycji mitologicznej i filozoficznej - Śpiewak, Sebastian (Folia Philosophica, 2018)
The aim of presented paper is to place the work of Xenophanes of Colophon in the history of Greek philosophy. His discovery of subjectivity of cognition might be taken as the next step in emancipation of logos from pre-philosophical way of understanding the world. The author broadens John Burnet’s interpretation of Xenophanes’ fragments, taking the general critique of earlier Greek thought — both mythological and philosophical (philosophy of physis) as its basis. Exemplification of Xenophanes’ modernisation of philosophical discourse is his understanding of truth, which he divides into two notions referring to the problem of subjectivity of cognition.